Peningkatan Profesionalisme Guru Pada Proses Pembelajaran Penididikan Agama Kristen Di SMTK Harapan Bangsa Sungai Rengas, Kalimantan Barat - Oktavianus, Oktavianus; Triposa, Reni; Arifianto, Yonatan Alex (Sekolah Tinggi Teologi Kanaan Nusantara, 2024)
Improving the professionalism of Christian religious education teachers is a crucial aspect in efforts to enhance the quality of Christian religious education in the school environment. Teacher professionalism encompasses various dimensions, including knowledge, skills, attitudes, and commitment to educational tasks. This research aims to investigate factors that can enhance the professionalism of Christian religious education teachers and its impact on student learning and development. This research method employs a qualitative approach, involving Christian religious education teachers from various educational levels. Data were collected through observation, interviews with teachers, and documentation. The research findings indicate that the improvement of professionalism among Christian religious education teachers at the Christian Theological High School Harapan Bangsa Sungai Rengas can be achieved through various strategies. Factors such as increased theological knowledge, development of teaching skills, participation in training and workshops, as well as the formation of a learning community among teachers, can positively contribute to teacher professionalism. Additionally, positive attitudes, high work ethics, and commitment to the development of student character are also key factors in enhancing the professionalism of Christian religious education teachers. The impact of this improvement in teacher professionalism is evident not only in the increased quality of Christian religious education but also in the moral and spiritual development of students. More professional teachers can create an inspirational learning environment, motivate students to develop spiritual values, and guide them in a deeper understanding of Christian religious teachings.AbstrakPeningkatan profesionalisme guru pendidikan agama Kristen merupakan suatu aspek krusial dalam upaya meningkatkan kualitas pendidikan agama Kristen di lingkungan sekolah. Profesionalisme guru mencakup berbagai dimensi, termasuk pengetahuan, keterampilan, sikap, dan komitmen terhadap tugas pendidikan. Penelitian ini bertujuan untuk menyelidiki faktor-faktor yang dapat meningkatkan profesionalisme guru pendidikan agama Kristen serta dampaknya terhadap pembelajaran dan perkembangan siswa. Metode penelitian ini menggunakan pendekatan kualitatif, melibatkan guru-guru pendidikan agama Kristen dari berbagai tingkat pendidikan. Data dikumpulkan melalui observasi, wawancara dengan guru dan dokumentasi. Hasil penelitian menunjukkan bahwa peningkatan profesionalisme guru pendidikan agama Kristen di Sekolah Menengah Teologi Kristen Harapan Bangsa Sungai Rengas dapat dicapai melalui berbagai strategi. Faktor-faktor seperti peningkatan pengetahuan teologis, pengembangan keterampilan mengajar, partisipasi dalam pelatihan dan workshop, serta pembentukan komunitas belajar antar guru dapat berkontribusi secara positif terhadap profesionalisme guru. Selain itu, sikap positif, etika kerja yang tinggi, dan komitmen terhadap pengembangan karakter siswa juga menjadi faktor kunci dalam meningkatkan profesionalisme guru pendidikan agama Kristen. Dampak dari peningkatan profesionalisme guru ini tidak hanya terlihat dalam peningkatan kualitas pembelajaran agama Kristen, tetapi juga dalam perkembangan moral dan spiritual siswa. Guru yang lebih profesional dapat menciptakan lingkungan belajar yang inspiratif, memotivasi siswa untuk mengembangkan nilai-nilai spiritual, dan membimbing mereka dalam memahami ajaran agama Kristen secara lebih mendalam.